2018
DOI: 10.1136/bmjopen-2018-021784
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbid conditions on outcomes of hip and knee replacement surgery: a systematic review and meta-analysis

Abstract: ObjectiveTo systematically perform a meta-analysis of the association between different comorbid conditions on safety (short-term outcomes) and effectiveness (long-term outcomes) in patients undergoing hip and knee replacement surgery.DesignSystematic review and meta-analysis.MethodsMedline, Embase and CINAHL Plus were searched up to May 2017. We included all studies that reported data to allow the calculation of a pooled OR for the impact of 11 comorbid conditions on 10 outcomes (including surgical complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 97 publications
4
93
1
1
Order By: Relevance
“…Comorbidities in patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA) are known to result in poor outcomes with longer hospital stays, increased hospital readmission rates and higher mortality rates [1]. Comorbidities previously reported for poor surgical outcomes in the setting of joint replacement surgery include obesity [2], cardiovascular disease [3], depression and other mental health disorders [4][5][6], diabetes mellitus [7][8][9], hepatic disease [10][11][12], and frailty [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidities in patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA) are known to result in poor outcomes with longer hospital stays, increased hospital readmission rates and higher mortality rates [1]. Comorbidities previously reported for poor surgical outcomes in the setting of joint replacement surgery include obesity [2], cardiovascular disease [3], depression and other mental health disorders [4][5][6], diabetes mellitus [7][8][9], hepatic disease [10][11][12], and frailty [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on joint replacement also show variations in the definitions and severity of comorbid disease [1], which may yield conflicting results, and consensus is still lacking among clinicians about the clinical indications for joint replacement surgeries [14], which may lead to differences in outcomes based on severity levels of associated comorbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…При том, что в целом десятилетняя выживаемость после первичного ТЭП ТБС весьма впечатляющая -95-97%*. Для определенных групп пациентов (очень молодые пациенты, пациенты с парами трения металл-металл, пациенты со сложной патологией, выраженной коморбидностью и прочие) эти показатели могут быть существенно хуже и снижаться до 70-80% в те же сроки [5,13,14,15,16,17,18,19,20], а результаты ревизий, и тем более повторных ревизий, вообще в отчетах регистров либо не представлены, либо отражены очень поверхностно [12,21,22]. ТРАВМАТОЛОГИЯ В свою очередь, исследования, посвященные оценке эффективности ревизионных операций, указывают на невозможность достичь такого же уровня успеха, как при первичном эндопротезировании [23,24,25].…”
unclassified
“…Patient comorbidities, 13 such as diabetes mellitus (DM), 14 previous cerebrovascular accident (CVA), or transient ischemic attack (TIA), 15 have also been proven to increase the risk of surgery failure due to infection or DVT after TKA; this results in postoperative complications and readmission within 30 days for further treatment. 8,16 In addition, some preoperative details can also negatively influence postoperative recovery. 17 For example, Leijtens et al 18 confirmed the correlation between perioperative bridging of anticoagulant therapy and high complication rate after total hip replacement (THR) and TKA.…”
mentioning
confidence: 99%